Active inductances controlled in GaAs MESFET technology - Benbouza, M.S.; Kenzai-Azizi, C.; Merabtine, N.; Saidi, Y.; Amourache, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Two new structures of active inductance which implement MESFET transistors are proposed in this article. The technological parameters of the components of “inductances” are those of 0.8 µm MESFET technology. We expose the advantages of these new structures such as the adjustable character of the value of the active inductance like their limitation, and we compare them to those of the literature.